The human CAS (cellular apoptosis susceptibility) gene mapping on chromosome 20q13 is amplified in BT474 breast cancer cells and part of aberrant chromosomes in breast and colon cancer cell lines. - Brinkmann, U; Gallo, M; Polymeropoulos, M H; Pastan, I

(untitled) (Genome Research, 1996)
The CAS (cellular apoptosis susceptibility) gene is the human homolog of the yeast chromosome segregation gene CSE1. CAS may have a dual function in mammalian cells, one in apoptosis and another in cell proliferation. We have now mapped the CAS gene to chromosome 20q13. This region is known to harbor amplifications that correlate with aggressive breast cancer. Southern hybridizations with a CAS cDNA fragment and fluorescent in situ hybridization (FISH) with a P1 clone containing the CAS gene show elevated copy numbers in one leukemia, three of four colon, and in three of seven breast cancer cell lines. Elevated CAS copy number in CEM leukemia and COLO201 colon cancer cells was attributable to additional copies of chromosome 20. In SW480 and COLO205 colon cancer cells CAS is part of aberrant chromosomes containing large parts of 20q. In breast cancer cells CAS is also part of aberrant 20q chromosomes (MDA-MB-157 and UACC-812) or of additional 20q isochromosome in MDA-MB-134. In MDA-MB361 and BT-474 breast cancer cells CAS is separated from other markers centromeric and telomeric of CAS on 20q. MDA-MB 361 contains one additional copy of CAS, separated from the centromeric 20q control probe. BT-474 cells have up to 12 additional CAS copies that we separated from nearby telomeric and centromeric probes on 20q and that are translocated to abnormal chromosomes.